Examining factors influencing employee job satisfaction in a hybrid work setting: a case study of an oil & gas company / Mohamad Fareezan Abdul Rasid, Mohd Azri Mohd Aris, Nik Harisha Qistina Nik Hamdi and Suriana Ramli - Abdul Rasid, Mohamad Fareezan; Mohd Aris, Mohd Azri; Nik Hamdi, Nik Harisha Qistina; Ramli, Suriana (2024)
The COVID-19 pandemic has presented unexpected challenges, compelling employees across the globe to change how they work. The widespread implementation of nationwide lockdowns has significantly accelerated the adoption and integration of technology, prompting firms to incorporate digital practices and processes into their operations swiftly. Post-pandemic, organizations are now more adept at a hybrid mode, allowing workers to operate remotely and in the office. Adjusting to this new norm may bring additional challenges for leaders and employees unfamiliar with working remotely. This study looks into the relationship between a hybrid working arrangement and employee job satisfaction, emphasizing changes in working conditions, work-life balance, and leadership influence. This study corresponds with Herzberg's Two Factor Theory, which was used in several studies to assess employee work satisfaction. The study employs a quantitative method, using a questionnaire. The survey was sent to 90 identified employees for a period of one month. After a series of follow-ups, 73 complete questionnaires were collected. Based on the data analysis of 73 respondents, it was discovered that working conditions, work-life balance, and leadership influence significantly influenced employee job satisfaction. Based on these findings, it is recommended that organizations create a conducive work environment by providing adequate space for flexible work, ensuring work-life balance by restricting leaders from assigning unnecessary tasks to employees beyond official working hours and emphasizing motivational support and clear performance goals. Future research should look into these qualities in different environments or types of firms.